2022
DOI: 10.1186/s13063-022-06504-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost-effectiveness of text messages with or without endowment incentives for weight management in men with obesity (Game of Stones): study protocol for a randomised controlled trial

Abstract: Background Obesity increases the risk of type 2 diabetes, heart disease, stroke, mobility problems and some cancers, and its prevalence is rising. Men engage less than women in existing weight loss interventions. Game of Stones builds on a successful feasibility study and aims to find out if automated text messages with or without endowment incentives are effective and cost-effective for weight loss at 12 months compared to a waiting list comparator arm in men with obesity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…A stakeholder workshop was used to decide on the final design. The final incentive design was tested in a feasibility trial (Dombrowski et al 2020) which showed promise, and a full definitive trial is in progress (Macaulay et al 2022). Three minor modifications were required, which endorse our approach to incentive design as fit for the purpose of effectiveness Firstly, all mention of charity donations was removed from information materials; secondly, the incentive provider named on the mock cheque was changed from University of Stirling to Game of Stones Research, as the intervention will be tested across the UK and men in other parts of the UK are likely to be unfamiliar with the University of Stirling; and, thirdly, an online audio-visual explanation of the incentive scheme was developed, in addition to the written participant information leaflet (see supplementary material).…”
Section: Discussionmentioning
confidence: 99%
“…A stakeholder workshop was used to decide on the final design. The final incentive design was tested in a feasibility trial (Dombrowski et al 2020) which showed promise, and a full definitive trial is in progress (Macaulay et al 2022). Three minor modifications were required, which endorse our approach to incentive design as fit for the purpose of effectiveness Firstly, all mention of charity donations was removed from information materials; secondly, the incentive provider named on the mock cheque was changed from University of Stirling to Game of Stones Research, as the intervention will be tested across the UK and men in other parts of the UK are likely to be unfamiliar with the University of Stirling; and, thirdly, an online audio-visual explanation of the incentive scheme was developed, in addition to the written participant information leaflet (see supplementary material).…”
Section: Discussionmentioning
confidence: 99%
“…Final follow-up occurred June 2023. The trial protocol can be found in Supplement 1 13 and the statistical analysis plan in Supplement 2. Eligible men were randomized to 1 of 3 groups: text messaging with financial incentives for 12 months; text messaging alone for 12 months, or waiting list (control) for 12 months.…”
Section: Trial Designmentioning
confidence: 99%